Network Biology Approaches to Achieve Precision Medicine in Inflammatory Bowel Disease - Thomas, John P; Modos, Dezso; Korcsmaros, Tamas; Brooks-Warburton, Johanne (Frontiers in Genetics, 2021)
Inflammatory bowel disease (IBD) is a chronic immune-mediated condition arising due to complex interactions between multiple genetic and environmental factors. Despite recent advances, the pathogenesis of the condition is not fully understood and patients still experience suboptimal clinical outcomes. Over the past few years, investigators are increasingly capturing multi-omics data from patient cohorts to better characterise the disease. However, reaching clinically translatable endpoints from these complex multi-omics datasets is an arduous task. Network biology, a branch of systems biology that utilises mathematical graph theory to represent, integrate and analyse biological data through networks, will be key to addressing this challenge. In this review, we provide an overview of the various types of network biology approaches that have been utilised in IBD thus far, including protein-protein interaction networks, metabolic networks, gene regulatory networks and gene co-expression networks. We also include examples of multi-layered networks that have combined various network types to gain deeper insights into IBD pathogenesis. Finally, we discuss the need to incorporate other data sources including metabolomic, histopathological, and high-quality clinical metadata. Together with more robust network data integration and analysis frameworks, such efforts have potential to realise the goal of precision medicine in IBD.